DESIGN OF STEEL STRUCTURE ELEMENTARY SCHOOL BUILDING SDN 05 PAGI IN CIBUBUR - Putri Ayu Widyaningrum; Sekar Mentari (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
Abstract—The compressive strength of concrete can be used to increase the strength of steel beams, especially in the positive moment region. From the composite action that occurs it is expected to reduce the size of the steel profile to be used. This thesis compiles a plan using Composite Steel Beams and End Plate Connections, using the SAP2000v23 program for static calculations, and calculation of beam and column dimensions as well as connection and base plate planning. To analyze the dimensions of the required WF Steel Profiles for Columns, Composite Beams, beam-column connections, main beams-joists, and floor slabs. From the analysis results, the dimensions for main beams are WF 400x200x8x13 and WF 450x200x9x14, for joists using WF 300x150x8x13, and for columns using WF 350x350x12x19. The design of the connection on the flanged beams uses an End Plate with a plate thickness of 18 mm and the number of bolts is 8 Ø 24 mm. The connection design for the web beam-column connection uses an End Plate with a thickness of 10 mm and a total of 8 Ø 20 mm bolts. The connection design for the main beam-subbeam and the joist beams uses an angled profile of 80x80x8 and the number of bolts is 4 Ø 22 mm. The required base plate size is 550x550x45mm using 8 Ø 19 mm anchors with a length of 800 mm. Keywords : Steel Structure, Composite, SAP2000v23